The effects of sulfated hyaluronan in breast, lung and colorectal carcinoma and monocytes/macrophages cells: Its role in angiogenesis and tumor progression. Issue 10 (26th February 2022) - Spinelli, Fiorella M.; Rosales, Paolo; Pluda, Stefano; Vitale, Daiana L.; Icardi, Antonella; Guarise, Cristian; Reszegi, Andrea; Kovalszky, Ilona; García, Mariana; Sevic, Ina; Galesso, Devis; Alaniz, Laura
Abstract: Hyaluronan (HA) is a component of the extracellular matrix (ECM) it is the main non‐sulfated glycosaminoglycan able to modulate cell behavior in the healthy and tumor context. Sulfated hyaluronan (sHA) is a biomaterial derived from chemical modifications of HA, since this molecule is not naturally sulfated. The HA sulfation modifies several properties of the native molecule, acquiring antitumor properties in different cancers. In this study, we evaluated the action of sHA of ~30–60 kDa with different degrees of sulfation ( 0.7 sHA1 and 2.5 sHA3) on tumor cells of a breast, lung, and colorectal cancer model and its action on other cells of the tumor microenvironment, such as endothelial and monocytes/macrophage cells. Our data showed that in breast and lung tumor cells, sHA3 is able to modulate cell viability, cytotoxicity, and proliferation, but no effects were observed on colorectal cancer cells. In 3D cultures of breast and lung cancer cells, sHA3 diminished the size of the tumorsphere and modulated total HA levels. In these tumor models, treatment of monocytes/macrophages with sHA3 showed a downregulation of the expression of angiogenic factors. We also observed a decrease in endothelial cell migration and modulation of the hyaluronan‐binding protein TSG‐6. In the breast in vivo xenograft model, monocytes/macrophages preincubated with sHA1 or sHA3 decreased tumor vasculature, TSG‐6 and HA levels. Besides, in silico analysis showed an association of TSG‐6, HAS2, and IL‐8 with biological processes implicated in the progression of the tumor. Taken together, our data indicate that sHA in a breast and lung tumor context is able to induce an antiangiogenic action on tumor cells as well as in monocytes/macrophages (Mo/MØ) by modulation of endothelial migration, angiogenic factors, and vessel formation .